2015
DOI: 10.7717/peerj.1050
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical students in Lahore, Pakistan towards the doctor–patient relationship

Abstract: Background. A good doctor–patient relationship is the centre stone of modern medicine. Patients are getting increasingly aware about exercising their autonomy and thus modern medicine cannot deliver all its advances to the patients if a good doctor–patient relationship is not established. We initiated this study with the aim to assess the leaning of medical students, who are the future physicians, towards either a doctor-centered or a patient-centered care, and to explore the effects of personal attributes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 19 publications
4
36
1
Order By: Relevance
“…With respect to gender, two studies from the United States [7] and Nepal [9] showed that female gender was more likely associated with higher PPOS scores when compared to the male gender. Conversely, a study from Pakistan [8] identified no statistical difference across gender.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…With respect to gender, two studies from the United States [7] and Nepal [9] showed that female gender was more likely associated with higher PPOS scores when compared to the male gender. Conversely, a study from Pakistan [8] identified no statistical difference across gender.…”
Section: Discussionmentioning
confidence: 91%
“…Haidet and colleagues showed that students in their earlier years of medical school (pre-clinical years) were more likely to have patient-centered attitudes than those in the later years of medical school (clinical years) [6]. On the other hand, a study from Pakistan by Ahmad and partners found an opposite result, where students in later academic years (clinical years) were more likely to exhibit patient-centered attitudes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In local context of Pakistan, literature reports a study that compared the effectiveness of simulated patients with real patients through mini-CEX to assess communication and clinical skills from student's perspective [34]. Another study conducted at Fatima Memorial Hospital (FMH) Medical and Dental College, where counseling skills were assessed of fourth year medical students using pre-recorded videos and role play showed an improvement in the communication skills of the medical students [14]. At Aga Khan University researchers compared examiner assessment with student self-assessment on communication skills using same rating scale on three OSCE stations [35].…”
Section: Role Of Feedback By Simulated Patientsmentioning
confidence: 99%
“…There is a dire need to enhance the communication skills amongst Pakistani medical students to meet the global criteria of patient centered doctors [14]. Until now, assessment of student's communication skills is in a preliminary stage in most of the medical schools in Pakistan [15] .It is a difficult task due to two main reasons; an increase in the number of medical students and additional responsibilities of the faculty such as educational work, research and health services.…”
mentioning
confidence: 99%